Challenges in the working relationship between professional nurses and clinical associates in selected district hospitals in South Africa - Emmah M. Mokoena; Tinda Rabie; Antoinette du Preez (AOSIS, 2023)
Background: Clinical associates were introduced in South Africa to address physician shortages in healthcare. Professional relationships between physicians and professional nurses (PNs) have been widely researched, but none specifically between the new cadre of clinical associates and PNs. Aim: This study aimed to understand the professional working relationship between PNs and clinical associates. Setting: Selected district hospitals within Mpumalanga Province, South Africa. Method: A qualitative descriptive design was used. Professional nurses were purposely sampled, and an all-inclusive sampling method was used for clinical associates in selected district hospitals within Mpumalanga Province, South Africa. Twelve (N = 12) semi-structured, individual interviews (PNs n = 6; clinical associates n = 6) guided by an interview guide were conducted in English. The interviews were audio recorded and transcribed verbatim by an independent transcriptionist. Tesch's eight steps of data analysis were employed to analyse the data. An independent co-coder assisted with data analysis. Results: This study yielded four themes: (1) professional relationship defined, (2) professional relationship characteristics, (3) professional challenges applicable to both PNs and clinical associates and (4) personal professional challenges applicable to clinical associates only. Conclusion: This study demonstrated that the professional relationships between PNs and clinical associates are affected by various challenges, which could be resolved within the department through in-service training and good communication. Contribution: This is one of the first studies that highlight the professional relationship challenges between PNs and clinical associates.